Expanding Disease Spectrum Associated With Puerperal Mastitis - McAdoo, Gregg L. (Hindawi Publishing Corporation, 1997)
Background: Staphylococcus aureus and the β-hemolytic streptococci are the commonest causes of puerperal mastitis which tends to be a localized disease process. This report describes 2 cases attributable to these bacteria that resulted in extramammary involvement and augmented morbidity. Cases: Two cases of postpartum mastitis are described, one leading to necrotizing fasciitis caused by group A streptococci and the other leading to toxic shock syndrome (TSS) caused by S. aureus. Conclusion: The spectrum of disease commonly attributed to mastitis occurring in this setting should be expanded.